Macrophage-Driven Biomaterial Degradation Depends on Scaffold Microarchitecture - Wissing, Tamar B.; Bonito, Valentina; van Haaften, Eline E.; van Doeselaar, Marina; Brugmans, Marieke M. C. P.; Janssen, Henk M.; Bouten, Carlijn V. C.; Smits, Anthal I. P. M. (Frontiers in Bioengineering and Biotechnology, 2019)
In situ tissue engineering is a technology in which non-cellular biomaterial scaffolds are implanted in order to induce local regeneration of replaced or damaged tissues. Degradable synthetic electrospun scaffolds are a versatile and promising class of biomaterials for various in situ tissue engineering applications, such as cardiovascular replacements. Functional in situ tissue regeneration depends on the balance between endogenous neo-tissue formation and scaffold degradation. Both these processes are driven by macrophages. Upon invasion into a scaffold, macrophages secrete reactive oxygen species (ROS) and hydrolytic enzymes, contributing to oxidative and enzymatic biomaterial degradation, respectively. This study aims to elucidate the effect of scaffold microarchitecture, i.e. µm-range fiber diameter and fiber alignment, on early macrophage-driven scaffold degradation. Electrospun polycaprolactone-bisurea (PCL-BU) scaffolds with either 2 or 6 μm (Ø) isotropic or anisotropic fibers were seeded with THP-1 derived human macrophages and cultured in vitro for 4 or 8 days. Our results revealed that macrophage-induced oxidative degradation in particular was dependent on scaffold microarchitecture, with the highest level of ROS-induced lipid peroxidation, NADPH oxidase gene expression and degradation in the larger fiber Ø anisotropic group. Whereas biochemically polarized macrophages demonstrated a phenotype-specific degradative potential, the observed differences in macrophage degradative potential instigated by the scaffold microarchitecture could not be attributed to either distinct M1 or M2 polarization. This suggests that the scaffold microarchitecture uniquely affects macrophage-driven degradation. These findings emphasize the importance of considering the scaffold microarchitecture in the design of scaffolds for in situ tissue engineering applications and the tailoring of degradation kinetics thereof.